Prehospital predictors for return of spontaneous circulation in traumatic cardiac arrest. Issue 3 (17th March 2022) - Benhamed, Axel; Canon, Valentine; Mercier, Eric; Heidet, Matthieu; Gossiome, Amaury; Savary, Dominique; El Khoury, Carlos; Gueugniaud, Pierre-Yves; Hubert, Hervé; Tazarourte, Karim
Abstract : Not-asystolic rhythms, spontaneous activity, gasping, ALS interventions (intravenous fluid resuscitation, packed red cells transfusion, external haemorrhage control) are associated with sustained return of spontaneous circulation in a national French cardiac arrest registry. Supplemental digital content is available in the text. Abstract : BACKGROUND: Traumatic cardiac arrests (TCAs) are associated with high mortality and the majority of deaths occur at the prehospital scene. The aim of the present study was to assess, in a prehospital physician-led emergency medical system, the factors associated with sustained return of spontaneous circulation (ROSC) in TCA, including advanced life procedures. The secondary objectives were to assess factors associated with 30-day survival in TCA, evaluate neurological recovery in survivors, and describe the frequency of organ donation among patients experiencing a TCA. METHODS: We conducted a retrospective study of all TCA patients included in the French nationwide cardiac arrest registry from July 2011 to November 2020. Multivariable logistic regression analysis was used to identify factors independently associated with ROSC. RESULTS: A total of 120, 045 out-of-hospital cardiac arrests were included in the registry, among which 4, 922 TCA were eligible for analysis. Return of spontaneous circulation was sustained on-scene in 21.1% (n = 1, 037) patients. Factors significantly associated with sustained ROSC were not-asystolic initial rhythms (pulseless electric activity (odds ratio [OR], 1.81; 95% confidence interval [CI], 1.40–2.35; p < 0.001), shockable rhythm (OR, 1.83; 95% CI, 1.12–2.98; p = 0.016), spontaneous activity (OR, 3.66; 95% CI, 2.70–4.96; p < 0.001), and gasping at the mobile medical team (MMT) arrival (OR, 1.40; 95% CI, 1.02–1.94; p = 0.042). The MMT interventions significantly associated with ROSC were as follows: intravenous fluid resuscitation (OR, 3.19; 95% CI, 2.69–3.78; p < 0.001), packed red cells transfusion (OR, 2.54; 95% CI, 1.84–3.51; p < 0.001), and external hemorrhage control (OR, 1.74; 95% CI, 1.31–2.30; p < 0.001). Among patients who survived (n = 67), neurological outcome at Day 30 was favorable (cerebral performance categories 1–2) in 72.2% cases (n = 39/54) and 1.4% (n = 67/4, 855) of deceased patients donated one or more organ. CONCLUSION: Sustained ROSC was frequently achieved in patients not in asystole at MMT arrival, and higher ROSC rates were achieved in patients benefiting from specific advanced life support interventions. Organ donation was somewhat possible in TCA patients undergoing on-scene resuscitation. LEVEL OF EVIDENCE: Prognostic and epidemiologic, Level III. Abstract :